2022
DOI: 10.1530/erc-22-0115
|View full text |Cite
|
Sign up to set email alerts
|

Association of DNA methylation with steroidogenic enzymes in Cushing’s adenoma

Abstract: DNA methylation and demethylation regulate the transcription of genes. DNA methylation-associated gene expression of adrenal steroidogenic enzymes may regulate cortisol production in cortisol-producing adenoma (CPA). We aimed to determine the DNA methylation levels of all genes encoding steroidogenic enzymes involved in CPA. Additionally, the aims were to clarify the DNA methylation-associated gene expression and evaluate the difference of CPA genotype from others using DNA methylation data. Twenty-five adrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The gene silencing caused by aberrant promoter methylation has been demonstrated in oncogenesis and progression, which showed the potential as a prognostic or therapeutic biomarker. [25][26][27] The present study identified that the promoter methylation levels of CSF3R…”
Section: Discussionmentioning
confidence: 51%
“…The gene silencing caused by aberrant promoter methylation has been demonstrated in oncogenesis and progression, which showed the potential as a prognostic or therapeutic biomarker. [25][26][27] The present study identified that the promoter methylation levels of CSF3R…”
Section: Discussionmentioning
confidence: 51%
“…It is noteworthy that promoter methylation plays an important regulatory role in gene expression [30][31][32]. Although previous studies have reported that MEF2C-AS1 was downregulated in DGC [27] and CC [28] lesion tissues, and BC [29] cells, the current study is the first that systematically described the MEF2C-AS1 methylation status and its influence on expression.…”
Section: Discussionmentioning
confidence: 83%